Analisis Perencanaan, Pelaksanaan, dan Evaluasi Problem Based Learning dan Project Based Learning - Firly Istiqomah; Ahmad Firdaus; Ratna Sari Dewi (Departement of Mathematics Education, 2023)
Problem-based learning and project-based learning are active learning models that aim to improve students' understanding and skills through engaged and in-depth learning experiences. The PBL model is student-centred learning, where learning begins by presenting students with a complex problem or real-world situation. Whereas PjBL is a learning approach where students learn through a significant project or task. The purpose of the research is to provide an overview of how the planning, implementation, and evaluation of learning using PBL and PjBL, because PBL and PjBL should be applied and developed in school learning. Because this will encourage students to be active and develop skills and critical thinking and also teachers can be trained to design problems and projects to meet student learning needs. The method used in developing this article is the literature study method, namely by reading writings from articles, books and other relevant writings. The results obtained from writing this article are that PBL and PjBL learning models can be applied in elementary schools, because these two models aim to activate the role of students in their learning, develop deeper understanding, as well as skills relevant to the real world and also support the development of students as active and independent learners